2007
DOI: 10.1007/bf03346328
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue, hepatic steatosis and obesity

Abstract: Human hepatic lipase (hHL) is mainly localized on the hepatocyte cell surface where it hydrolyzes lipids from remnant lipoproteins and high density lipoproteins and promotes their hepatic selective uptake. Furthermore, hepatic lipase (HL) is closely associated with obesity in multiple studies. Therefore, HL may play a key role on lipid homeostasis in liver and white adipose tissue (WAT). In the present study, we aimed to evaluate the effects of hHL expression on hepatic and white adipose triglyceride metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…In a few studies, an association between echocardiographic SAT thickness and insulin resistance has been reported in obese adult patients. 8,20 Another adult study indicated that higher SAT thickness is associated with impaired fasting glucose in non-diabetic men and women. 9 In another study, Iacobellis et al showed that echocardiographic SAT thickness correlated significantly in multivariate analysis with waist circumference, DBP and fasting insulin, although TGs and HDL cholesterol were not independently related to SAT thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies, an association between echocardiographic SAT thickness and insulin resistance has been reported in obese adult patients. 8,20 Another adult study indicated that higher SAT thickness is associated with impaired fasting glucose in non-diabetic men and women. 9 In another study, Iacobellis et al showed that echocardiographic SAT thickness correlated significantly in multivariate analysis with waist circumference, DBP and fasting insulin, although TGs and HDL cholesterol were not independently related to SAT thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Perivascular adipose tissue (PVAT) surrounds the blood vessels. EAT mass and diameter are increased in obesity 109, 110 , and the volume of PVAT is associated with visceral obesity 111 . Neither, EAT nor PVAT, are separated by a fascial layer from the surrounding tissue.…”
Section: Insulin Resistancementioning
confidence: 99%
“…EAT mass and thickness are increased in obesity [28], showing a stronger correlation with abdominal fat accumulation [29]. Increased EAT thickness or volume has also been shown to correlate with components of the metabolic syndrome, including fasting plasma glucose and insulin levels, insulin resistance (assessed by euglycemic hyperinsulinemic clamp or surrogate indices like HOMA and QUICKI), atherogenic lipid profile and systolic blood pressure [30,31].…”
Section: Eat As Marker Of Ectopic Fat and Metabolic Derangementsmentioning
confidence: 99%